DINAMIKA PERKEMBANGAN HARGA KOMODITAS CABAI MERAH (Capsicum annuum L) DI KABUPATEN JEMBER - maya eka nurvitasari; Anik Suwandari; Luh Putu Suciati (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
Red chili prices in the market tend fluctuate over time. Development of red chilli in centers production included at Jember Regency continue to be made, but production still fluctuate and have not been able to meet market demand. Condition fluctuation production with uncertainty price needs to corrected immediately. Information of price and production need as solution to cope with fluctuation of red chili price. The research method used analytical descriptive method. Location chosen by purposive method at Jember Regency. The research used secondary time series data 2012 until 2016. Analytical tools used probability analysis and plot, trend analysis, and multiple linear regression analysis with double log model. The results showed that (1) production and prices red chili fluctuate every quarterly. The highest red chili price at farmers and consumers level occurred in the fourth quarter and the lowest in the second quarter. Red chili highest production in fourth quarter and lowest in first quarter. (2) Trend production and prices of red chili on 2017 until 2018 fluctuated and increased. (3) Factors that significantly affect of red chili supply are red chili production in previous month and harvested area.